Knowledge Sharing Implications of the Emergence of GPT Chat on Learning Methods at SMP 4 Muhammadiyah Depok, West Java - Laode Muhamad Fathun; Chiara Vincha; Aisha Saharani; Algis Zalita Pitra (Peneliti Teknologi Teknik Indonesia, 2023)
This presentation aims to describe the activities of the Community Partnership Program or PKM carried out at SMP 4Muhammadiyah Depok, West Java. This activity took the topic of the Contribution and implications of Chat GPT to learning methods in the digital era. This activity is carried out by socialization, discussion and practice methods. The result obtained was that Chat GPT turned out to greatly influence the learning method at SMP 4 Muhammadiyah Depok. Teachers worry about their students not using technology wisely. To overcome these problems, our team provides hands-on practice in the responsible and plagiarism-free use of GPT Chat. In addition, we also provide the practice of making power points to teachers so that the material provided to students can be more interesting in learning. GPT chat has both positive and negative impacts depending on how humans use it.